Nunavut: un esfuerzo hacia el entendimiento étnico - Morales Gómez, Jorge (Boletín Museo del Oro, 2003)
En 1993, el gobierno de Canadá y la etnia Inuit acordaron crear una nueva provincia, llamada Nunavut, nuestra tierra. Por su administración, los Innuit reciben 1.1 billones de dólares canadienses durante 14 años pero no harán más reclamos de tierras en Canadá. Los Inuit de Nunavut tienen planes de manejo de fauna y están invirtiendo en nuevas empresas propias, con el apoyo del gobierno, pues crear fuentes de empleo es una prioridad. Nunavut es una oportunidad para rescatar prácticas de caza y pesca en un nuevo contexto, y se espera un renacer del esencialismo étnico. El gobierno canadiense y los Inuit demuestran así que las minorías étnicas pueden ser dueñas de su propio destino. Abstract In 1993, the Government of Canada and the Inuit people signed an agreement for the creation of a new territory, called Nunavut, our land. By this, Inuit besides receive 1.1 billion dollars (can.) during 14 years for its administration, but decline any other land claim in Canada. Nunavut Inuit have developing plans of wildlife management and harvesting for them, and they are investing in trusts and enterprises of their own, with federal supporting. Employment is an urgent need for Nunavut. In this paper I argue that Nunavut is a valid opportunity for rescuing hunting and fishing practices in a new context, and that it will improve directly Inuit ethnic essentialism. Canadian government and Inuit demonstrate that ethnic minorities may be owners of their destiny.